2002
DOI: 10.1046/j.1365-2036.2002.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Mono, dual and triple moxifloxacin‐based therapies for Helicobacter pylori eradication

Abstract: Background: Moxifloxacin is a broad spectrum fluoroquinolone with single daily administration, currently used, above all, for respiratory tract infections. Aim: To compare the efficacy of different 1‐week moxifloxacin‐based Helicobacter pylori eradication regimens. Methods: One hundred and twenty H. pylori‐positive subjects were randomized to receive moxifloxacin (400 mg/day), moxifloxacin (400 mg/day) and lansoprazole (30 mg/day) or moxifloxacin (400 mg/day), lansoprazole (30 mg/day) and clarithromycin (500 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…1). Of seven potential eligible articles, we excluded two more articles as the moxifloxacin-based therapy was used as second-line treatment for Helicobacter pylori infection (23,26) and one paper without standard triple therapy as contrast group (24). Finally, four RCTs (n=772 patients) were included which compared moxifloxacin-based triple therapy to clarithromycin-based triple therapy (21,27,29,35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Of seven potential eligible articles, we excluded two more articles as the moxifloxacin-based therapy was used as second-line treatment for Helicobacter pylori infection (23,26) and one paper without standard triple therapy as contrast group (24). Finally, four RCTs (n=772 patients) were included which compared moxifloxacin-based triple therapy to clarithromycin-based triple therapy (21,27,29,35).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years new treatment schemes based on fluoroquinolones have been under investigation (21)(22)(23)(24)(25)(26)(27)(28)(29); however, first-generation fluoroquinolones such as norfloxacin and pefloxacin did not show satisfactory eradication rates (30,31). Several studies have evaluated the efficacy of different levofloxacin-based triple therapies and shown eradication rates up to 90% (22,27).…”
Section: Introductionmentioning
confidence: 99%
“…The principal effort of recent clinical trials is to offer new options for treatment of the infection to avoid resorting to rescue therapies [8]. Previous reports have demonstrated that fluoroquinolone-based triple regimens may provide important options for the treatment of H. pylori infection [9][10][11]. In particular, 1-week PPI/levofloxacin-based triple therapies have proven to have good efficacy in the treatment of H. pylori infection [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…In early studies, promising eradication rates of about 90% in the first-line therapy of H. pylori were reported [Nista et al 2005;Di Caro et al 2002a]. …”
Section: Introductionmentioning
confidence: 99%